Exploitation of heterosis in two line hybrids for different physio-chemical traits - L.Mahalingam and N. Nadarajan (Electronic Journal of Plant Breeding, 2010)
Four aromatic varieties viz., ADT 41, Pusa Basmati 1, Basmati 370 and Taroari Basmati and the three TGMS lines (TS29, TS 6, and GD 98013) were crossed to generate 12 F1 hybrid with normal fertility. Observations were recorded forquality characters viz., head rice recovery, kernel length, kernel breadth, L/B ratio, linear elongation ratio, amylosecontent, gel consistency, alkali digestion and volume expansion ratio and grain yield per plant. Overall two hybrids TS29 x ADT 41 and TS 29 x Pusa Basmati 1 were found to be superior and could be utilized commercially for exploitationof heterosis.